PEMANFAATAN DHARMAGITA DALAM MENINGKATKAN MINAT BELAJAR BAHASA BALI PADA GENERASI MUDA DI DESA ADAT SADING KECAMATAN MENGWI KABUPATEN BADUNG - Ni Putu Ayuni Setia Putri; Gusti Nyoman Mastini; I Made Luwih (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT The declining interest of young people in learning the Balinese language due to technological advancements, globalization, and changes in modern lifestyles has become a major challenge in preserving the Balinese language and culture. This study aimed to describe youths' perceptions of Dharmagita in Balinese language learning, identify the challenges encountered in learning Dharmagita, and analyze its utilization in enhancing interest in learning the Balinese language among youths in Desa Adat Sading, Mengwi District, Badung Regency. This study employed a descriptive qualitative approach. Data were collected through observations, interviews, documentation, and literature review involving youths, Dharmagita instructors, and traditional village authorities as informants. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that Dharmagita serves as an effective learning medium by integrating vocal arts, literary values, religious teachings, Balinese vocabulary, traditional expressions, and authentic cultural experiences. Its implementation increases students' interest in learning the Balinese language, fosters pride in local culture, and strengthens the cultural identity of the younger generation. The study also identified several challenges, including limited learning time, insufficient understanding of Kawi and classical Balinese vocabulary, the influence of popular culture and technology, inadequate supporting facilities, and inconsistent guidance from families, schools, and the community. It can be concluded that Dharmagita plays a strategic role as a contextual, creative, and culturally oriented medium for preserving the Balinese language while strengthening the cultural identity of younger generations. ABSTRAK Menurunnya minat generasi muda dalam mempelajari bahasa Bali akibat perkembangan teknologi, globalisasi, dan perubahan gaya hidup modern menjadi tantangan dalam upaya pelestarian bahasa dan budaya daerah. Penelitian ini bertujuan mendeskripsikan persepsi yowana terhadap Dharmagita dalam pembelajaran bahasa Bali, mengidentifikasi kendala yang dihadapi dalam mempelajari Dharmagita, serta menganalisis pemanfaatannya dalam meningkatkan minat belajar bahasa Bali pada yowana di Desa Adat Sading, Kecamatan Mengwi, Kabupaten Badung. Penelitian menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui observasi, wawancara, dokumentasi, dan studi kepustakaan. Informan penelitian meliputi yowana, pembina Dharmagita, dan pihak desa adat. Data dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa Dharmagita merupakan media pembelajaran yang efektif karena mengintegrasikan seni suara, sastra, nilai religius, kosakata, ungkapan tradisional, serta pengalaman budaya secara langsung sehingga mampu meningkatkan minat belajar bahasa Bali, menumbuhkan kebanggaan terhadap budaya lokal, dan memperkuat identitas budaya generasi muda. Kendala yang dihadapi meliputi keterbatasan waktu, rendahnya pemahaman bahasa Kawi dan kosakata Bali klasik, pengaruh budaya populer dan teknologi, keterbatasan sarana pendukung, serta belum optimalnya pembinaan dari keluarga, sekolah, dan masyarakat. Penelitian ini menyimpulkan bahwa Dharmagita memiliki peran strategis sebagai media pembelajaran bahasa Bali yang kontekstual, kreatif, dan berorientasi pada pelestarian bahasa serta penguatan identitas budaya generasi muda.